Sistem Pendukung Keputusan Penerimaan Bantuan Bedah Rumah Menggunakan Metode Weight Product (WP) Dan Simple Additive Weighting (SAW) (Studi Kasus : Desa Semuli Raya Kecamatan Abung Semuli) - Ferry Susanto; Agnes Yulia Putri Nukahayubun; Endang Endang (Institut Bakti Nusantara, 2020)
Semuli Raya Village in the process of selecting home renovations only relies on data collected and does not use criteria or methods, but instead uses conditions obtained from prospective recipients of house renovation assistance, so as to determine who is entitled to receive assistance the results are not in accordance with reality which exists. Citizens who have the right do not get aid as they should, whereas the rich get help. Based on the above problems, a decision support system is needed to help determine the recipient of home improvement assistance using the Weight Product (WP) and Simple Additive Weighting (SAW) methods and using assessment criteria, namely, housing conditions, home status, employment, monthly income and number of occupants